Preventing hamstring injuries - Part 2: There is possibly an isometric action in the hamstrings in high speed running and it does matte - Van Hooren, B.; Bosch, F. (Sport Performance & Science Reports, 2018)
We thank Shield and Murphy (1) for promoting discussion on our articles (2 3), hereby providing us an opportunity to clarify and elaborate on our arguments and hopefully forward the eld of hamstring injury prevention. Most prominently, Shield and Murphy state that recommendations to employ an isometric hamstring training approach instead of an eccentric one is premature and they state that we presented no evidence from human studies showing that hamstring fascicles behave isometrically in running. Here we will respond to both points as well as several other points.